2014
DOI: 10.1371/journal.pone.0099216
|View full text |Cite
|
Sign up to set email alerts
|

Mapping B-Cell Epitopes for the Peroxidoxin of Leishmania (Viannia) braziliensis and Its Potential for the Clinical Diagnosis of Tegumentary and Visceral Leishmaniasis

Abstract: The search toward the establishment of novel serological tests for the diagnosis of leishmaniasis and proper differential diagnosis may represent one alternative to the invasive parasitological methods currently used to identify infected individuals. In the present work, we investigated the potential use of recombinant peroxidoxin (rPeroxidoxin) of Leishmania (Viannia) braziliensis as a potential antigen for the immunodiagnosis of human tegumentary (TL) and visceral leishmaniasis (VL) and canine visceral leish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…Tryparedoxin peroxidase belongs to a family of proteins called peroxiredoxins, which are associated with parasite virulence and have a high antigenicity during the active disease. Previous studies have shown the antigenicity of peroxiredoxins in dogs and humans infected by Leishmania infantum or L. braziliensis (46,47). Khosravi et al showed that a realtime PCR using the tryparedoxin peroxidase gene was specific for CL diagnosis (48).…”
Section: Discussionmentioning
confidence: 99%
“…Tryparedoxin peroxidase belongs to a family of proteins called peroxiredoxins, which are associated with parasite virulence and have a high antigenicity during the active disease. Previous studies have shown the antigenicity of peroxiredoxins in dogs and humans infected by Leishmania infantum or L. braziliensis (46,47). Khosravi et al showed that a realtime PCR using the tryparedoxin peroxidase gene was specific for CL diagnosis (48).…”
Section: Discussionmentioning
confidence: 99%
“…The reaction was stopped after 30 min with 4 N H 2 SO 4 , and the absorbance was measured at 450 nm. For the depletion ELISA, the sera was incubated in peptide-coated and blocked plates at a 1∶100 dilution overnight at 2–8°C [23] , [24] . Depleted and undepleted samples were transferred to plates coated overnight with r CatL (50 ng/well) and blocked.…”
Section: Methodsmentioning
confidence: 99%
“…The Bio-Manguinhos EIE-LVC kit is recommended by the Brazilian Ministry of Health for diagnosis of VL in dogs [44]. However, comparative serological studies have shown that the EIE-LVC kit needs to be used in conjunction with another diagnostic method to reduce false-positive results and to compensate for high potential for cross-reactivity [45,46].…”
Section: Figmentioning
confidence: 99%